A Comparative Study of Open-Source Digital Library Software: Designing a Model Selection Criterion - Ajimuddin, S. K. Md.; Jana, Sibsankar; Khatun, Samima (Journal of Information and Knowledge, 2023)
Every organization and institute is using various software for day-to-day functions and activities. The libraries are no exception. To give better library services and to satisfy growing users’ demands, designing a digital library is essential. There are various digital library software packages in the public domain. This study has attempted to compare popular open-source digital library software and design standard selection criteria for the same.